Comparison of Plasma Amino Acid Levels of Two Breeds of Japanese Native Chicken and a Commercial Layer Line - Takawaki, Minani; Tanizawa, Hiroshi; Nakasai, Eriko; Shiraishi, Jun-ichi; Kawakami, Shin-Ichi; Oka, Takao; Tsudzuki, Masaoki; Bungo , Takashi (International Journal of Poultry Science, 2013)
The objective of the present study was to conduct amino acid profiling of two Japanese indigenous hens (Tosa-jidori; TJI and Ukokkei; UKO) and compared with a commercial hen (JL). Asparagine, leucine and proline levels in commercial layers were higher than those in both native Japanese chickens. Lysine and glutamate in UKO were higher than those in others and taurine was also higher than in JL. Serine in UKO was lower than those in others and methionine and cysteine were also lower than in JL. Arginine in TJI was lower than those in JL and UKO. No significant differences between breed/line were observed in histidine, threonine, glutamine, glycine, alanine, valine, isoleucine, tyrosine, phenylalanine and tryptophan. These results suggest that levels of dietary amino acid requirements might be different between native Japanese chickens.